Decision Support System in Choosing The Quality of Charcoal Briquettes from Coconut Shell to Improve The Quality and Maximised by The Method of Analytical Hierarchy Process (the case study in Padang pariaman) - Ilham Siregar; Wahyuni Yahyan; Danyl Mallisza (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2019)
The regency of Padang Pariaman is one of the centres of the plantation to the plant oil in the region of West Sumatra. Many find various types of plant oil that spread in every area. Decision-Making system (DSS) should be able to understand the problems that exist that are the basis for the decision (the decision Maker) to determine the priority of the selection and determine the type of charcoal coconut charcoal quality to be used as briquettes. This study obtained the top Level (Goal) is the selection of Charcoal Material priorities approved as the purpose of this study. The Level of the heart (the Criterion) in the hierarchy that shows the criteria that the Color of the Skin, Coconut Fiber, Coconut Shell, water Content, Coconut Meat. The lowest Level (Alternatives) in the hierarchy that shows the alternate choice of the Type of Coconut, which is helpful as briquettes, that Old Coconut, Coconut Koreang, Coconut Mudang, Young Coconut. Of the highest rank possessed by the alternatives is the type of Old Coconuts (0.600) and second by the kind of Coconut Koreang 2 (0.242), the Type of Coconut 3 Coconut Mudang (0.113) and ranking low is a Young Coconut (0.046) as a material consideration in the manufacture of charcoal quality then in the analysis, the priority is the “Old Palm” Keywords: Coconut, Briquettes, Shell, DSS, AHP